Analysis Of Bacterial Contamination By Total Plate Number (ALT) Method In Smoked Fish At One Of The Market Traders: Analisis Cemaran Bakteri Metode Angka Lempeng Total (ALT) pada Ikan Asap di Salah Satu Pedagang Pasar - Safitri, Yunita Diyah; Widodo, Wimbuh Tri; Azizah, Yunita Dwi Nur (Medicra (Journal of Medical Laboratory Science/Technology), 2023)
Bacterial contamination can come from the environment as a result of food production processes in the form of biological, chemical and foreign matter contaminants that can interfere with, harm and endanger human health. One of the problems in the processed food sector is the high level of bacterial contamination in the food served on the market. The condition of open food is also the main factor causing food to be contaminated with bacteria. The Total Plate Count (ALT) or total plate count (TPC) is an examination used to determine the number of microorganisms both bacteria and fungi using solid media with the final result being colonies. The aim of the study was to determine bacterial contamination and to determine the total plate number (ALT) of bacterial colonies in smoked fish sold at Ngemplak Market, Tulungagung. This research used a Simple Random Design (RAS) method with four treatments and 3 repetitions. The results showed that for menot fish it was 16.2 x 105 cfu/g, for tuna it was 10.5 x 105 cfu/g, for tuna it was 9.4 x 105 cfu/g, for bader fish it was 16.4 x 105 cfu/g. g, and in whitefish 20.5 x 105 cfu/g. The conclusion is that the bacterial contamination of smoked fish sold at the Ngemplak Market using the ALT method exceeds the normal limit value set by SNI 2725:2013.